The impact of a psychological training program on developing self-confidence among basketball seniors players ( field study of Msila basketball clubs) - Filali, mohamed; benhamed, nouredinne (sports creativity, 2025)
This current research aims to identify the impact of psychological training program on the self-confidence of basketball players, and to identify also the differences between players in developing self-confidence. The researcher used the experimental approach in the manner of two equal groups (control and experimental). The research sample included 20 players from basketball clubs of Msila :(10) Players from the Msila Union Basketball Club (seniors), and (10) Players from the Msila Youth Basketball Club (seniors). The researcher conducted the preliminary test using the self-confidence measure, then he implemented the program that consists of (16) Units, and after completing the application of the program, The researcher conducted the post-tests, where the applied program had a positive impact on developing self-confidence among the study sample. The researcher had highly recommended that the program should be adopted in developing self-confidence and pay attention to the psychological side that is related to all different kinds of basketball